2007
DOI: 10.1007/s10681-007-9556-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of genetic diversity in safflower genotypes using agro-morphological traits and RAPD markers

Abstract: This research was conducted to study the genetic diversity in safflower (Carthamus tinctorius L.) using agro-morphological traits and RAPD markers. Sixteen selected lines derived from landraces growing in various agro-climatic regions of Iran along with four exotic genotypes were evaluated in a randomized complete block design with three replications under field conditions. Days to emergence, days to initial flowering, days to flowering, days to maturity, plant height, branches per plant, capitula per plant, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 23 publications
8
51
1
2
Order By: Relevance
“…However, several genotypes were more productive than the check variety which produced 1.3 t/ha. Narrower variation ranges were reported in previous studies, from 1.5 to 2.7 t/ha (Panahiet al, 2013) and from 1.1 to 2.2 t/ha (Amini et al, 2007).…”
Section: Morphological Parameters:-supporting
confidence: 45%
See 1 more Smart Citation
“…However, several genotypes were more productive than the check variety which produced 1.3 t/ha. Narrower variation ranges were reported in previous studies, from 1.5 to 2.7 t/ha (Panahiet al, 2013) and from 1.1 to 2.2 t/ha (Amini et al, 2007).…”
Section: Morphological Parameters:-supporting
confidence: 45%
“…Res. 5(7), 926-934 927 of the world (Amini et al, 2007). In comparison with other oilseed crops, safflower is characterized by high adaptation ability in regions where winter months are cool and summer months are arid (Erbas et al, 2016).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…The weight of 1000-seed varies between 15-104 g with a hull percentage that varies between 18-59% of seed weight (Smith, 1996;Bowles et al, 2010). It has been emphasized in several studies that these characteristics are influenced by genetic variation (Smith, 1996;Amini et al, 2008;Ben Moumen et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Mahasi et al, (2009) and Khan et al, (2009) found out 61 and 78 amplified fragments from 14 and 15 RAPD primers and noticed 1-10 and 3-16 RAPD fragments generated per primer with an average of 5.5and 9.5 bands in safflower, respectively. On safflower same work was reported by Amini et al, (2008), and Souframanien and Gopalakrishna (2004) by using 15 and 25 RAPD primers which produced total polymorphic 132 and 44 bands and calculated amplified products range from 3 to 9 through standard of 1.8 and 13 bands for each primer, respectively.…”
Section: Rapd Analysismentioning
confidence: 56%